Analysis of Ground Current Return Composition at Metro Traction Substations under AC Power Supply System - LI Kunpeng; LIU Li; ZHAO Yunyun; WANG Lingxiao; HE Zhujun; CAO Xiaobin (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] To enhance the intercity commuting capacity, newly built city rapid transit lines adopt a 27.5 kV AC (alternating current) traction power supply system, enabling higher operating speed. While improving train transport capacity, AC traction power supply also increases external leakage currents, resulting in excessive ground return currents. Therefore, it is necessary to conduct an in-depth research on ground return current composition in metro line main substations using AC power supply system. [Method] Focusing on a city rapid rail transit line in Guangzhou that adopts AC traction power supply system, the composition and ground return path of current return system at the traction substations that supply power to both stations and depots is studied. To determine the proportion of ground return current within the total return current, tests on return current are conducted during the joint commissioning and testing phase before the line opened. The return current of traction substation is tested, the wiring layouts are investigated on-site, and current measurements of the copper-clad steel grounding body are performed. On this basis, tests on earth soil return currents are conducted, and improvement measures for ground return are proposed. [Result & Conclusion] The primary reason for excessive ground return current at the main substation is the presence of return current through copper-clad steel structures. In addition to the known station and depot cable returns and earth soil returns, there exists an additional return path through cable trench supports, accounting for more than 25% of the traction current flowing back to the traction substation grounding grid via this path, thereby leading to larger results from ground return current measurements. After implementing the proposed improvement measures, the proportion of current returning through earth soil decreased to approximately 30% of the total return current, achieving an excellent level of ground return quality.